PELATIHAN DASAR ATLETIK NOMOR LARI PADA MAHASISWA PRODI PRNJASKESREK UNIVERSITAS ISLAM INDRAGIRI - Rahmad Yulmiando; ANDRIANSYAH (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2021)
Athletics is a sport that consists of a combination of various types of physical sports such as running, jumping, throwing, and walking. downstream and to be prepared for the 2022 provprov event in Kuansing, Riau province. The sample in this service is all 20 athletic students. The success of the organizers of community service activities is the involvement of the training participants, especially UNISI Physical Education and Health students, seen from the results of the evaluation during the implementation of the activity, namely: persistence and involvement of trainees in getting involved in the implementation of athletic sports training activities provided, mastery of students in understanding concepts and the basic techniques of athletics.